Factors Influencing the Effective Leadership Succession Planning: Study on A Malaysian GLC - Abdul Shukor, Shamsulkahar; Hussain, Suhaidah (KnE Social Sciences, 2019)
Factors influencing effective Leadership Succession Planning (LSP) of one main Malaysian Government Linked Companies (GLC) becomes the focal scope of this research paper. The need to understand external factors, among others, on Malaysian economic policy itself, has a great influence on LSP program. It is not sufficient for the leaders in GLCs to only master their business operations knowhow. With the great interest to discover the actual practice of a successful GLC, researcher took this subject as this qualitative research is aimed to study the current factors and the gap that is influencing the effectiveness of current LSP initiatives by a service-oriented of GLC, and to highlight some key critical factors as proposed in the literature. Factors influencing the effectiveness of LSP are also subject on the ability of the leaders to adopt to external changes particularly in the era of a borderless economic and faster rate of technology changes, and there are some differences among the industries and organizations, subject to the nature of the business and their stakeholders. Nevertheless, some important concept in LSP can be used as guidelines and practices be it from the primary data or the research literature. In view of this, the researcher is determined to conduct a qualitative study in meeting the research objectives and to answer the research questions. An interview with the Group Chief Executive Officer (CEO) of one GLC, who is the subject matter expert. The recording from the interview was transcribed and further analyzed using ATLAS.ti software. The findings evidence that there is the current practice of leadership succession planning in the company, anyhow there is a gap between the aspirations of the Group CEO and the availability of C-level replacement from within, and between the reality and the theories. Results of the findings identify the outcomes that need to be taken into action for a more effective LSP program. In the future, similar research approach can be conducted to other GLCs in order to analyze the similarities and complementary aspirations with regards to LSP.